Sandponics: A Sustainable Agriculture Solution for Food Security and Resource Efficiency in Arid Regions - Chythra Somanathan Nair; Meera Bakheet Hamad Alsudain; Ramya Manoharan; Drishya Nishanth; Radhakrishnan Subramanian; Anicet Manga; Abdul Jaleel (Journal of Sustainable Agriculture and Environment)
ABSTRACT Agriculture in arid regions encounters significant challenges, including water scarcity, poor soil quality and low crop yields. Sandponics, also known as the Integrated Aqua Vegeculture System (IAVS), presents a promising solution by utilizing sand as a sustainable, water‐efficient medium for food production. This review explores the potential of sandponics as a scalable, eco‐friendly agricultural practices in arid regions. Sand, being abundant, recyclable and cost‐effective, offers a viable alternative to conventional growth media, making sandponics a practical and resource‐efficient option. The method has demonstrated success in enhancing crop productivity, particularly, in saline environments, while minimizing environmental impact. Sandponics supports food security and land use optimization by transforming challenging conditions into productive agricultural landscapes. Future research should focus on refining sand selection, optimizing nutrient and environmental conditions, managing microbial interactions and scaling up sandponics for broader application, thus advancing their role in sustainable agriculture.